A low-cost hardware implementation of a software run logic analyzer for the DLSU ECE laboratory: A project study - Ajon, Marco (Animo Repository, 1986)
A logic analyzer is a digital troubleshooting equipment. It becomes an indispensable tool especially when correcting timing problems in digital circuits. It is especially useful in debugging timing errors in microprocessor-controlled, circuits. Although it may be argued that a simple oscilloscope would solve any problem, this is a fallacy: First, an oscilloscope only display two channels. What happens now if one was trying to check on several signals? Second, even a multi-trace oscilloscopes will make viewing difficult for every fast system clock rates. Third, unless an oscilloscope conditions the inputs fed into it, such as having the signals pass through Schmitt triggers, errors may appear at the CRT when there are none, or may not appear when there surely are. Useful as it is, the cost of a commercial logic analyzer is very much prohibitive, even for a school like DLSU. These units cost anywhere from P100,000 to P3,000,000 each. This thesis-project therefore, has been dedicated by the group to the DLSU-ECE Laboratory. The particular aim by the group is for the circuit to be easily available for use by other ECE students at present and in the future in their study of digital electronics.